TRANSLANGUAGING IN ACTION: REIMAGINING LANGUAGE CLASSROOM ASSESSMENT - Ande, Pradeep (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper explores the use of translanguaging in multilingual classrooms, focusing on its integration into assessment practices to enhance narrative writing skills. It outlines a translanguaging-based assessment approach that allows students to utilise their entire linguistic repertoire during the learning process. Key phases of this approach include planning, data collection, feedback, and reflection, emphasising a dynamic, personalised evaluation method. The paper also introduces a rubric tailored to assess content, linguistic resources, and grammar within a translanguaging framework. Drawing on theoretical insights from scholars like Canagarajah and García, the proposed methodology supports a fluid use of languages, fostering a more inclusive, effective learning environment. Implications include reducing language anxiety, leveraging native languages for better comprehension, and challenging monolingual biases.